An analysis of translation techniques for racist utterances in Rush Hour 3 - Jonathan Haryana; Muhammad Aprianto Budhie Nugroho; Wulan Rahmatunisa (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2024)
This study aims to analyse the translation of racist content in the movie subtitles of